Mendudukkan Kembali Makna Kafir dalam al-Qur’an dan Konteksnya secara Teologis, Sosiologis, dan Politis - Moh. Isom Mudin; Nurul Laili Ahmadah; Muhamad Fawwaz Rizaka; Rahmat Ardi Nur Rifa Da’i (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2021)
To this day, the word kafir is still a hot topic to be discussed. Lately, the recommendation of the prohibition to mention kafir for non-Muslims to maintain religious harmony and peace in society has reaped pros and cons among Muslims. And in fact today, among the wider community, accusations of being infidels against a person or group are increasingly rife with the concept of kafir which is only understood about someone who believes in God other than Allah. This narrow understanding has given birth to existing conflicts, even though the concept of kafir has actually existed since the time of the Prophet and was not a problem among religious communities. Basically, the Qur'an itself has discussed the meaning of kafir and its levels. So to get a comprehensive understanding requires a relevant and in-depth approach. Through a qualitative library research, the researchers discuss the meanings of kafir contained in the Qur'an and the extent to which a person can be considered as an infidel according to the Qur'an as a guide for Muslims. Sampai saat ini kata kafir masih menjadi perbincangan hangat. Belakangan ini anjuran pelarangan penyebutan kafir bagi non muslim untuk menjaga kerukunan dan ketentraman umat beragama menuai pro dan kontra di kalangan umat Islam. Dan faktanya, dewasa ini di kalangan masyarakat luas tuduhan kafir terhadap seseorang atau kelompok semakin marak dengan konsep kafir yang hanya dipahami tentang seseorang yang beriman kepada Tuhan selain Allah. Pemahaman yang sempit ini telah melahirkan konflik-konflik yang ada, padahal konsep kafir sebenarnya sudah ada sejak zaman Nabi dan tidak menjadi masalah di kalangan umat beragama. Pada dasarnya Al-Qur'an sendiri sudah membahas tentang pengertian kafir dan tingkatannya. Sehingga untuk mendapatkan pemahaman yang komprehensif diperlukan pendekatan yang relevan dan mendalam. Melalui penelitian pustaka kualitatif, peneliti membahas tentang makna kafir yang terkandung dalam Al-Qur'an dan sejauh mana seseorang dapat dianggap kafir menurut Al-Qur'an sebagai pedoman bagi umat Islam.